Extracellular matrix remodelling is associated with muscle force increase in overloaded mouse plantaris muscle. (5th September 2020) - Stantzou, A.; Relizani, K.; Morales‐Gonzalez, S.; Gallen, C.; Grassin, A.; Ferry, A.; Schuelke, M.; Amthor, H.
Abstract : Aims: Transforming growth factor‐β (TGF‐β) signalling is thought to contribute to the remodelling of extracellular matrix (ECM) of skeletal muscle and to functional decline in patients with muscular dystrophies. We wanted to determine the role of TGF‐β‐induced ECM remodelling in dystrophic muscle. Methods: We experimentally induced the pathological hallmarks of severe muscular dystrophy by mechanically overloading the plantaris muscle in mice. Furthermore, we determined the role of TGF‐β signalling on dystrophic tissue modulation and on muscle function by (i) overloading myostatin knockout ( Mstn −/− ) mice and (ii) by additional pharmacological TGF‐β inhibition via halofuginone. Results: Transcriptome analysis of overloaded muscles revealed upregulation predominantly of genes associated with ECM, inflammation and metalloproteinase activity. Histology revealed in wild‐type mice signs of severe muscular dystrophy including myofibres with large variation in size and internalized myonuclei, as well as increased ECM deposition. At the same time, muscle weight had increased by 208% and muscle force by 234%. Myostatin deficiency blunted the effect of overload on muscle mass (59% increase) and force (76% increase), while having no effect on ECM deposition. Concomitant treatment with halofuginone blunted overload‐induced muscle hypertrophy and muscle force increase, while reducing ECM deposition and increasing myofibre size. Conclusions: ECM remodelling is associated with an increase in muscle mass and force in overload‐modelled dystrophic muscle. Lack of myostatin is not advantageous and inhibition of ECM deposition by halofuginone is disadvantageous for muscle plasticity in response to stimuli that induce dystrophic muscle. Abstract : Overload induced muscle dystrophy causes extracellular matrix remodelling as seen by upregulation of genes associated with the gene ontology (GO)‐terms "collagen metabolism", "metalloproteinases", and "inflammatory response". These changes go in parallel with a more than twofold increase in muscle force and muscle weight.